(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article analyzes the administrative structure of the Fergana Valley during the time of Amir Temur and the Timurids based on Zahiriddin Muhammad Babur’s work “Baburnama”. The information presented in “Baburnama” was compared through other historical sources, as well as opinions expressed in scientific literature. It is shown that the Fergana valley is divided into bekliks, and the bekliks are divided into orchins, and preliminary conclusions about the administrative boundaries of each beklik and orchin are given.